Novel application of a Fe-Zn double-metal cyanide catalyst in the synthesis of biodegradable, hyperbranched polymers - Sebastian, Joby; Srinivas, Darbha (Chemical Communications, 2011)
The use of Fe-Zn double-metal cyanide as a solid catalyst for synthesizing biodegradable, hyperbranched polymers from diacids and glycerol has been reported, for the first time, wherein acidity, micro-mesoporosity and hydrophobicity of the catalyst played an important role in controlling gelation.